Perforated neonatal appendicitis: A rare presentation of Hirschsprung disease - Viknesh Subramaniam; Mohd Shahrulsalam Mohd Shah; Wan Abdul Rahman Wan Faiziah (Elsevier, 2021)
Acute appendicitis is the most common diagnosis of an acute abdomen in children, however, it is extremely rare in neonates. Premature infants are more predisposed to the condition with increased rate of perforation causing peritonitis. The diagnosis is usually delayed and more often made during laparotomy or autopsy.Here, we report a baby girl with uneventful antenatal history was brought to the emergency department on day 15 of life with intestinal obstruction symptoms who was initially thought to have intussusception or small bowel volvulus. The infant was brought in for surgery and intraoperatively, a perforated appendix was found. Appendicectomy and peritoneal washout was performed. Post-operatively, the infant had persistent ileus and remain refractory to treatment with antibiotics and prokinetics. A re-laparotomy was done with colostomy and serial biopsies of large bowel. The histopathological examination of the biopsies could not exclude Hirschsprung disease. Then, rectal suction biopsy was performed prior to discharge and the acetylcholinesterase (ACH) enzyme study revealed a strong positivity for Hirschsprung disease. The infant subsequently underwent laparoscopic assisted transanal pull-through at 5 months old. The histopathological examination of the continuous section from anus to mid-transverse colon showed devoid of ganglion cells.In conclusion, neonatal appendicitis is a rare condition with atypical presentation and high rate of morbidity and mortality. It is paramount to have a high index of suspicion and it should be included in the differential diagnosis of an infant presenting with an acute abdomen with vague symptoms and signs.